Alasan Unilever Melakukan Kerja Sama dengan PT. Perkebunan Nusantara Terkait Percepatan Produksi Minyak Sawit Berkelanjutan Tahun 2018 - Dwira Angganita, I Gusti Ayu; Kumala Dewi, Putu Ratih; Widya Nugraha, A.A Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2021)
This research aims to describe what is the reason for Unilever to cooperate with PT Perkebunan Nusantara (PTPN) regarding the acceleration of sustainable palm oil production in 2018, using descriptive qualitative methods. The cooperation between Unilever and PTPN is the first produce-protect model on a large scale that Unilever has been able to implement. The signing of the Memorandum of Understanding (Mou) shows Unilever's reason, considering that the land area and palm oil production of PTPN is the lowest compared to the private and community plantations. Therefore, this research uses the framework of dependency and multinational companies to answer what is the reason for Unilever in the cooperation with PTPN. This research then found the existence of internal and external factors that causes of dependence which are the reasons Unilever cooperates with PTPN. Keywords: Dependency, PT Perkebunan Nusantara, Sustainable Palm Oil, Unilever